Docking and molecular dynamics studies of potential new leads against DBL3x derived from chondroitin sulfate A (CSA): a new approach for the treatment of malaria - Spadeto, Joao P M; Cormanich, Rodrigo A; Franca, Tanos C C; LaPlante, Steven R; Goncalves, Arlan S (Journal of biomolecular structure & dynamics, 2022)
In this work the DBL3x domain of the erythrocyte membrane protein from Plasmodium Falciparum (PfEMP1), was revisited as a potential molecular target for the development of new drugs against malaria. This protein interacts with chondroitin sulfate A (CSA), a glycosaminoglycan present in the substance fundamental for connective tissues of vertebrates and is implicated in malaria complications in pregnant women. We performed molecular docking and molecular dynamic studies of DBL3x complexed with CSA and five analogues, where the sulfate group was replaced by phosphate, in order to evaluate if the better electrostatic interactions provided by phosphate groups could afford better binders capable of preventing the binding of CSA to DBL3x. Results suggest that all proposed compounds have high affinity towards DBL3x and could bind better to the DBL3x domain of PfEMP1 than CSA, qualifying as potential inhibitors of this protein and, therefore, new potential leads for the drug design against malaria.Communicated by Ramaswamy H. Sarma.
Keywords: malaria; molecular docking; Animals; Molecular Dynamics Simulation; Plasmodium falciparum; protozoální proteiny; Female; Glycosaminoglycans; tropická malárie; Malaria, Falciparum; glykosaminoglykany; ženské pohlaví; simulace molekulového dockingu; antigeny protozoální; erytrocyty; Sulfates; Protozoan Proteins; Malaria; sírany; Placenta; lidé; chondroitinsulfáty; simulace molekulární dynamiky; parazitární komplikace těhotenství; těhotenství; membránové proteiny; Chondrointin derivatives; Chondroitin Sulfates; Phosphates; Antigens, Protozoan; Erythrocytes; Membrane Proteins; molecular dynamics; zvířata; Pregnancy; malárie; placenta; fosfáty; Molecular Docking Simulation; Pregnancy Complications, Parasitic; Humans